2003
DOI: 10.1021/es034357p
|View full text |Cite
|
Sign up to set email alerts
|

Subspecies-Level Variation in the Phytoextraction of Weathered p,p‘-DDE by Cucurbita pepo

Abstract: Previous studies indicate that Cucurbita pepo can phytoextract highly weathered persistent organic pollutants (POPs) from soil and translocate large quantities to aerial tissues. To investigate intraspecific variability in uptake potential, a field study was conducted to quantify the phytoextraction of weathered p,p'-DDE by 21 cultivar varieties of summer squash from two distinct subspecies, C. pepo ssp texana and C. pepo ssp pepo. Significant differences exist between the two subspecies, with average root and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
35
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(47 citation statements)
references
References 55 publications
9
35
0
3
Order By: Relevance
“…Moreover, subspecies-level variation in phytoextraction of DDE by C. pepo has been reported. 10) Structure-selective accumulation has also been observed for chlordane 11) and dioxins and dioxin-like compounds.…”
Section: )mentioning
confidence: 98%
“…Moreover, subspecies-level variation in phytoextraction of DDE by C. pepo has been reported. 10) Structure-selective accumulation has also been observed for chlordane 11) and dioxins and dioxin-like compounds.…”
Section: )mentioning
confidence: 98%
“…This suggests that root exudates and endophyte population may be the dominant mechanisms affecting the variation in uptake between the two cultivars of lettuce. Organic acid exudates has been shown to play a key role in persistent organic contaminant uptake in 21 cultivars of squash from soil (White et al, 2003b) and differences in exudates between cultivars has also been demonstrated in rice (Aulakh et al, 2001). The mechanisms responsible for cultivar-specific differences in antimicrobial uptake in lettuce merits additional research.…”
Section: Antimicrobials In Lettuce and Soilmentioning
confidence: 99%
“…2B). The band intensities and the BCFs of PCDDs and PCDFs and phytoextraction of p,p9-DDE were also significantly positively correlated (White et al, 2003;Matsuo et al, 2011; r = 0.711 for PCDDs, r = 0.742 for PCDFs, and r = 0.780 for p,p9-DDE, P , 0.05 in all cases; Supplemental Fig. S2).…”
Section: Sds-page For Xylem Sapmentioning
confidence: 81%
“…Previous studies reported that members of the Cucurbitaceae family, particularly C. pepo, which includes pumpkin and zucchini, accumulated higher levels of PCDDs and PCDFs (Hülster et al, 1994;Inui et al, 2008), 2,2-bis(p-chlorophenyl) 1,1-dichloroethylene (p,p9-DDE; White et al, 2003), PCBs (Aslund et al, 2008;Inui et al, 2008), chlordane (Mattina et al, 2004), and drins (Otani et al, 2007) compared with the levels in other plant species. Thus, it appears that the Cucurbitaceae family has unique mechanisms of POP uptake and translocation.…”
mentioning
confidence: 96%